Competitive Advantage Strategies to Improve the Business Performance of PT. XYZ's Cosmetic Products - Oki Permanakusumah; Faizatun; Deriawan (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
This study aims to analyze and formulate a competitive business strategy for PT. XYZ to enhance its corporate performance. The research employs a qualitative descriptive method with a quantitative approach. Primary data were obtained through FGDs and in-depth interviews with ten informants, while secondary data were sourced from literature and company reports. Data processing involved four interrelated methods: the IFE and EFE matrices to analyze internal and external factors, the SWOT, IE, and Grand Strategy matrices to determine alternative business strategies, and the QSPM method to establish strategic priorities. The findings indicate that PT. XYZ's strategies include affordable pricing, product variations, branding, and extensive distribution. Internal and external factor analysis resulted in IFE and EFE scores of 2.60, placing the company in the